THE IMPACT OF DIGITALIZATION ON THE SALES PERFORMANCE OF MSMES IN MEDAN CITY - Pasaman Silaban; Frederick Saroha Silaban; Sherina Yohana Sitompul (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Digital transformation has become an important factor in modern marketing strategies, including for Micro, Small, and Medium Enterprises (MSMEs). This study analyzes the effect of digitalization implementation through the use of social media, marketplaces, and digital payment systems on the sales performance of MSMEs in Medan City. The method used is a quantitative approach with a survey technique of 150 MSME players from various sectors, supported by the Partial Least Square (PLS) method with the help of SmartPLS version 3 software. The results show that digitalization contributes significantly to increasing sales volume, expanding market reach, and improving transaction process efficiency. Social media is the most influential channel in attracting new customers, while digital payments have been proven to increase consumer convenience and transaction frequency. However, some MSME players still face obstacles in digital literacy and online promotion costs. These findings emphasize the importance of digital training and government policy support to strengthen the competitiveness of MSMEs in the era of a technology-based economy. Keywords: Usage of E-Commerce; Usage of QRis; Digital Transformation; MSME Sales Performance